Penerapan Media Tanggaris (Ular Tangga Hubungan antar Garis) dengan TaRL untuk Meningkatkan Hasil Belajar Siswa SD - Rani Aryanti Rukmana; Fatimah Azzahroh; Nabila Hasri Ainun (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2026)
Teacher-centered learning is often less optimal because it does not sufficiently account for differences in students’ developmental stages and levels of understanding and tends to maintain theoretical, traditional methods. This study aimed to assess the effectiveness of the Tanggaris media (Ular Tangga Hubungan Antar Garis) combined with the Teaching at the Right Level (TaRL) approach in improving students’ understanding of the concept of relationships among lines in Mathematics. The study employed a quantitative pre-experimental one-group pretest–posttest design involving 23 third-grade students at a public school in Bogor City. The research instrument was a 10-item multiple-choice test administered before and after the intervention, while data analysis was conducted using the Shapiro–Wilk normality test, N-Gain calculation, and a paired-samples t-test. The normality test results indicated that the data were normally distributed, with pretest significance of 0.321 > 0.05 and posttest significance of 0.069 > 0.05. The mean student score increased from 57.8 on the pretest to 81.7 on the posttest, with an N-Gain value of 0.5330, indicating moderate effectiveness. The paired-samples t-test showed a significance value (2-tailed) of 0.000 < 0.05; thus, the alternative hypothesis was accepted, indicating that the use of Tanggaris media with the TaRL approach had a significant effect on students’ learning outcomes. Accordingly, the implementation of TaRL-based Tanggaris media was effective in improving students’ understanding of relationships among lines and making the learning process more adaptive and meaningful.